Daftar istilah industri perkhidmatan kewangan bahasa Inggeris-bahasa Melayu. (Kuala Lumpur Dewan Bahasa dan Pustaka, 2001)
Dictionary of financial services industry terms.
Includes bibliographical references (p. 825).
Keywords: Business -- Dictionaries; Economics -- Dictionaries; English language -- Dictionaries -- Malay; Finance -- Dictionaries; Tariff -- Dictionaries